Heard on the Birdline, July 1-October 15, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Summary of the Iowa Birdline update for July 1-October 15, 1994. Highlights of the update were mostly all water related, including reports of three Common Black-headed Gulls, an adult Long-tailed Jaeger, a Pacific Loon, and a Fulvous Whistling Duck. Other interesting observations included nesting Barn Owls and a family of Burrowing Owls seen in August, and Sharp-tailed Sparrow and Parasitic Jaeger sightings in September. Epson - sheet feed